Hubungan Kandungan Fluorida Pada Air Sumur Gali Dan Kebiasaan Menggosok Gigi Terhadap Karies Gigi Pada Siswa MIN 2 Muara Enim - Eka Herlina; Deli Lilia (Poltekkes Kemenkes Tasikmalaya, 2023)
Dental caries is a type of disease that can be found in individuals of various age groups, especially in children throughout the world. The aim of this research was to determine the relationship between fluoride content in dug well water and personal hygiene on dental caries in MIN 2 students in Muara Enim. The research design used is a cross-sectional research design. The population in this study included 195 students in grades 2 and 3 who attended MIN 2 Muara Enim. From the results of the analysis, it was found that out of 130 respondents, 61 (46.9%) had fewer dental caries compared to 69 (53.1%) who had no dental caries. From the results of the analysis, it is known that the proportion of 130 respondents who found that the fluoride content in dug well water did not meet the requirements was 80 (61.5%) more than the 50 (38.5%) whose fluoride content in dug well water met the requirements. There were 81 (62.3%) respondents with bad tooth brushing habits compared to 49 (37.7%) respondents with good tooth brushing habits. The Chi square test results obtained a value of 0.011 < (0.05). This means that there is a significant relationship between the fluoride content in dug well water and dental caries in MIN 2 students in Muara Enim. Likewise, the results obtained for the tooth brushing variable with dental caries in MIN 2 students in Muara Enim had a ρ value of 0.000 < (0.05).